The role of judges on the commencement of reorganization proceedings - Lucas, E Saute Ana Juliana De Sales (Department of Commercial Law, 2023)
This dissertation aims to elaborate on the role of judges on the commencement of judicial reorganisation proceedings under the Mozambican new insolvency and business reorganisation law. An application to enter reorganization proceedings suspends all actions and executions for debt collection against the applicant interfering with his creditors' and other intervenor's rights. Debtors who are not facing distress can apply to enter reorganization proceedings in order to enjoy the stay of actions and executions, abusing court processes and causing harm to creditors. Judges play an important role preventing abuse of court processes by preliminary dismiss applications that lack material and formal requirements. they can produce evidence on their own motion by appointing an expert to examine and verify the truth of the facts, arguments and evidence presented by the applicant as to justify his or her right to enter reorganisation proceedings. Key words: insolvency law, reorganisation proceedings, commencement of reorganisation proceedings, abuse of process, suspension of actions and executions, preliminary dismissal, the role of judges.